2007
DOI: 10.1086/511279
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolar Sexual Lubricant Causes Epithelial Damage in the Distal Colon: Potential Implication for HIV Transmission

Abstract: Rectally applied hyperosmolar gels induce greater epithelial denudation and luminal secretion than iso-osmolar gels. Because denudation plausibly increases the risk of HIV transmission, hyperosmolar gels make poor rectal microbicide formulations, and hyperosmolar sexual lubricants may increase susceptibility to HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
124
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(132 citation statements)
references
References 30 publications
4
124
2
Order By: Relevance
“…Despite these clinical findings as well as publications associating the use of hyperosmolar products rectally with mucosal damage, 20 TFV 1% gel was not associated with any significant index of mucosal damage overall. 35 Using paired t-tests, some rectal-secretion cytokines (IL-1b, TNFa, IL-6, MIP-1a; all often classified as ''pro-inflammatory'' were shown to be reduced in the TFV-treated groups at different study stages.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Despite these clinical findings as well as publications associating the use of hyperosmolar products rectally with mucosal damage, 20 TFV 1% gel was not associated with any significant index of mucosal damage overall. 35 Using paired t-tests, some rectal-secretion cytokines (IL-1b, TNFa, IL-6, MIP-1a; all often classified as ''pro-inflammatory'' were shown to be reduced in the TFV-treated groups at different study stages.…”
Section: Discussioncontrasting
confidence: 65%
“…18 Despite this, there were no significant differences in genital tract adverse events (AEs) in clinical trials of this formulation. 14,19 However, given that hyperosmolar products can induce mucosal damage in the colon, 20,21 they require careful phase 1 evaluation if they are to be considered as candidate RMs.…”
mentioning
confidence: 99%
“…25 Despite the enhanced comfort and pleasure lubricants afford, recent literature has highlighted the enhanced risk they may also confer. 22 Laboratory research has shown that many of these agents compromise the integrity of the epithelial lining of the rectum and colon, which could increases susceptibility to infection, 20,21,24,39 and that several products even amplify HIV replication in vitro. 20 Notably, research to date exploring lubricant as a mechanism of HIV/STI transmission has largely focused on PAI risk as it pertains to the receptive partner, and it is therefore unknown whether lubricants enhance susceptibility of the insertive partner's penis to infection.…”
Section: Calabrese Et Almentioning
confidence: 99%
“…18 Moreover, documentation of condom use often relies on aggregate retrospective self-reports, which have proven vulnerable to distortion, with MSM more commonly underestimating than overestimating unprotected PAI. 19 Additionally, Black MSM's participation in other behavioral practices known or suspected to influence vulnerability to HIV and other STIs, including lubricant use [20][21][22][23][24] and precoital rectal douching or enema use, [25][26][27][28][29][30] has received insufficient attention in the literature.…”
mentioning
confidence: 99%
“…14,15 Regarding colon vs. vaginal pharmacology issues, the 1% TFV gel dosed rectally in RMP-02/MTN-006 resulted in higher colon tissue TFV concentrations compared to vaginal tissue TFV concentrations after vaginal dosing in other studies. 13,[16][17][18] This difference is likely due to increased colorectal mucosal absorption of TFV secondary to single columnar histology in the colon compared to the multilayer stratified squamous epithelium in the vagina.…”
mentioning
confidence: 94%